A new species of Passiflora supersection Tacsonia (Passifloraceae) from Amazonas, Northern Peru - Esquerre-Ibañez, Boris (Phytotaxa, 2015)
A new species, Passiflora kuethiana (Passifloraceae) is described and illustrated from Cordillera Calla Calla, Amazonas Department, Northern Peru. This species shares morphological characteristics more related with Passiflora tripartita and Passiflora runa on stipules and flowers but differs mainly from the former in the size, shape and color of the involucre, peduncles length and arrangement, and the latter in shape and margin of stipules. This species is considered as a new endemic to the Peruvian flora. Its location within the section Elkea according to the new classification of Passiflora is proposed. Comparative data of related species and a key to the species of the section Elkea from Northern Peru are too added.